The CERDIK Movement: A Health Promotion and Disease Prevention Approach to Non-Communicable - Dewi nur Sukma Purqoti; supriyadi supriyadi; Baiq Rulli Fatmawati (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2026)
Non-Communicable Diseases (NCDs) are the leading cause of morbidity and mortality in Indonesia and are largely associated with unhealthy lifestyles, including physical inactivity, unhealthy dietary patterns, smoking, inadequate rest, and poor stress management. Limited public knowledge regarding NCD risk factors remains a major challenge in disease prevention. This community service program aimed to improve public knowledge on NCD prevention through the implementation of the CERDIK program, which consists of regular health check-ups, avoiding cigarette smoke, engaging in regular physical activity, maintaining a balanced healthy diet, getting adequate rest, and managing stress effectively. The program employed health education through interactive lectures, group discussions, question-and-answer sessions, educational media distribution, and evaluation using pretest and posttest assessments. The activity was conducted in collaboration with a Community Health Center (Puskesmas) as the implementing partner. The evaluation results indicated that prior to the intervention, all participants (100%) had a low level of knowledge, whereas after the educational intervention, all participants (100%) achieved a high level of knowledge. These findings demonstrate that the CERDIK health education program effectively improved community knowledge regarding NCD prevention. This program is expected to serve as an initial step in promoting sustainable healthy lifestyle behaviors, reducing NCD risk factors, and strengthening health promotion and disease prevention programs at the primary healthcare level. Furthermore, collaboration between universities and Community Health Centers is expected to enhance the sustainability of community empowerment initiatives in NCD prevention.